2011
DOI: 10.1136/ard.2011.155044
|View full text |Cite
|
Sign up to set email alerts
|

Human leucocyte antigen risk alleles for psoriatic arthritis among patients with psoriasis

Abstract: Certain HLA-B and HLA-C alleles confer susceptibility to PsA among patients with psoriasis and may be used to identify patients with PsC who may develop PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 42 publications
9
100
0
5
Order By: Relevance
“…HLA-C*06 is the strongest genetic risk factor for psoriasis and also predisposes to earlier onset and more severe disease [53,54]. HLA-B alleles are associated with musculoskeletal manifestations and HLA-B*27, *B38, B*39 and B*08 were reported as specific genetic markers for PsA among patients with psoriasis, while HLA-C*06 has been associated with lower risk of developing PsA [55]. They reported that HLA-C*06 and DR*07 were associated with fewer damaged and involved joints (OR 0.59 for the presence of both alleles).…”
Section: Predictors Of Treatment Responsementioning
confidence: 97%
“…HLA-C*06 is the strongest genetic risk factor for psoriasis and also predisposes to earlier onset and more severe disease [53,54]. HLA-B alleles are associated with musculoskeletal manifestations and HLA-B*27, *B38, B*39 and B*08 were reported as specific genetic markers for PsA among patients with psoriasis, while HLA-C*06 has been associated with lower risk of developing PsA [55]. They reported that HLA-C*06 and DR*07 were associated with fewer damaged and involved joints (OR 0.59 for the presence of both alleles).…”
Section: Predictors Of Treatment Responsementioning
confidence: 97%
“…6,8 A recent large fine-mapping study of psoriatic disease within the MHC region using an HLA-variant imputation approach, has shed new light regarding HLA associations within this region for PsV and PsA. 9 In this elegant study, Okada and colleagues 9 defined the 4-digit HLA allele and amino acid resolutions.…”
Section: Major Histocompatibility Complex Associations In Psoriatic Dmentioning
confidence: 98%
“…The highest positive predictive value is noted with HLA-B27, which is present in up to 50% of patients with psoriatic arthritis. 6 Histologically, synovial infl ammation in psoriatic arthritis has many similarities to rheumatoid arthritis. Both feature increased levels of activated T cells and infl ammatory cytokines and mediators, such as tumor necrosis factor (TNF)-alpha, interleukin (IL)-17, IL-23, and other cytokines.…”
Section: Management Of Patients With Psoriatic Arthritismentioning
confidence: 99%